2019
DOI: 10.1029/2018jd029562
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variations of Ambient Concentrations of Trace Elements in a Highly Polluted Region of China

Abstract: Anthropogenic emissions of trace elements (TEs) into the atmosphere have warranted global concern due to their adverse effects on human health and the ecosystem. We adapted the Weather Research and Forecasting (WRF) and Models‐3/Community Multiscale Air Quality (CMAQ) modeling system to predict the spatial and temporal concentrations of 11 TEs (arsenic, selenium, lead, cadmium, chromium, nickel, antimony, manganese, cobalt, copper, and zinc) in fine particulate matter (PM2.5) in January, April, July, and Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…Statistical analysis showed that the revised CMAQ model has acceptable performance with respect to V and Ni predictions, and the simulated Ni level is similar to that reported in Liu et al. (2019).…”
Section: Resultssupporting
confidence: 81%
“…Statistical analysis showed that the revised CMAQ model has acceptable performance with respect to V and Ni predictions, and the simulated Ni level is similar to that reported in Liu et al. (2019).…”
Section: Resultssupporting
confidence: 81%
“…China is the country with the world’s largest coal consumption, averaging approximately three billion tons of coal annually in recent years 22 , and contributing nearly 80% of the national SO 2 emission 23 . As companion emitters, atmospheric heavy metals (including TMIs) from coal combustion are present in much higher concentrations in northern China than in developed countries 24 26 . Traditionally, S(IV) could be oxidized by TMIs in cloud/fog water 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Nickel et al (2017) simulated the heavy metal concentrations in moss across Europe, as they are toxic to plants (Nagajyoti et al, 2010). Tian et al (2015) developed an anthropogenic emission inventory of toxic heavy metals of TSPs in China, which was evaluated by a transport model and observation data in a highly polluted region of Northern China (Liu et al, 2019). Ying et al (2018) developed both anthropogenic and natural (mineral dust [MD]) inventories of hazardous trace elements in China and evaluated by a transport model and observation data in mega cities in China such as Beijing, Nanjing, and Chengdu.…”
Section: Introductionmentioning
confidence: 99%